2008
DOI: 10.1097/aln.0b013e31818a37dc
|View full text |Cite
|
Sign up to set email alerts
|

Metoclopramide Does Not Attenuate Cricoid Pressure–induced Relaxation of the Lower Esophageal Sphincter in Awake Volunteers

Abstract: The current investigation demonstrates that cricoid pressure reflexly decreases LES tone and barrier pressure in awake subjects. Although metoclopramide increased LES and barrier pressures, it did not attenuate cricoid pressure-induced relaxation of the LES and barrier pressures and thus seems to have no value in preventing gastroesophageal reflux during cricoid pressure. Metoclopramide may be useful in preventing reflux when there is need to release or discontinue cricoid pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
0
12
2
Order By: Relevance
“…However, there are also concerns that CP may promote vomiting by causing relaxation of the lower oesophageal sphincter, 58,59 an effect which cannot be attenuated by the prior administration of metoclopramide. 60 Initially confirmed in awake volunteers, recent work on anaesthetised patients has suggested the effect is pronounced, with an overall 29% decrease in lower oesophageal sphincter pressure and a 44% reduction in barrier pressure. 61 Cadaver studies and case reports have shown that rupture of the oesophagus may occur secondary to CP.…”
Section: Does Cp Contribute To Adverse Events?mentioning
confidence: 98%
“…However, there are also concerns that CP may promote vomiting by causing relaxation of the lower oesophageal sphincter, 58,59 an effect which cannot be attenuated by the prior administration of metoclopramide. 60 Initially confirmed in awake volunteers, recent work on anaesthetised patients has suggested the effect is pronounced, with an overall 29% decrease in lower oesophageal sphincter pressure and a 44% reduction in barrier pressure. 61 Cadaver studies and case reports have shown that rupture of the oesophagus may occur secondary to CP.…”
Section: Does Cp Contribute To Adverse Events?mentioning
confidence: 98%
“…The authors concluded that Metoclopramid may have a role in increasing barrier pressure when the cricoid pressure is not applied or has to be released. 88 Studies using advanced imaging techniques such as MRI and CT scanning have shown the oesophagus to be displaced laterally rather than occluded with the cricoid pressure 89,90 [III]. Smith et al, 89 in a recent study of healthy volunteers, using MRI scanning, found the oesophagus to be displaced laterally in over half of the patients without cricoid pressure, increasing to 90.5% when cricoid pressure was applied.…”
Section: Efficacy Of the Cricoid Pressurementioning
confidence: 99%
“…The physiological response to applied cricoid pressure deserves some mention. Application of the cricoid pressure has been shown to lower the LES tone and may be a contributing factor facilitating regurgitation and aspiration 78,87,88 [V]. Metoclopramid increases LES pressure but a recent study failed to show a benefit in terms of overcoming the cricoid pressure-induced lowering of the LES tone.…”
Section: Efficacy Of the Cricoid Pressurementioning
confidence: 99%
“…14,15 Although metoclopramide has been reported to increase LES pressure, its effects on EGJ compliance have not been evaluated. [4][5][6][7][8] Therefore, the aim of the present study was to investigate the effects of metoclopramide on esophageal motor activities and EGJ compliance in healthy volunteers, for which we employed the EndoFLIP system and high-resolution 36-channel manometry.…”
Section: 13mentioning
confidence: 99%
“…As a result, metoclopramide augments gastrointestinal motility and enhances gastric emptying, and also increases lower esophageal sphincter (LES) tone. [4][5][6][7][8] It has recently been reported that esophageal motor activities and compliance of the esophagogastric junction (EGJ) is important for prevention of gastroesophageal reflux, with the latter considered to cause greater volume reflux of gastric contents into the esophagus. [9][10][11] Fundoplication surgery for repairing the EGJ has been consistently shown to prevent pathological gastroesophageal reflux by restoration of normal EGJ compliance.…”
Section: Introductionmentioning
confidence: 99%